2018
DOI: 10.1101/317693
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased excitation-inhibition ratio stabilizes synapse and circuit excitability in four autism mouse models

Abstract: SummaryDistinct genetic forms of autism are hypothesized to share a common increase in excitation-inhibition (E-I) ratio in cerebral cortex, causing hyperexcitability and excess spiking. We provide the first systematic test of this hypothesis across 4 mouse models (Fmr1 -/y , Cntnap2 -/-, 16p11.2 del/+ , Tsc2 +/-), focusing on somatosensory cortex. All autism mutants showed reduced feedforward inhibition in layer 2/3 coupled with more modest, variable reductions in feedforward excitation, driving a common incr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 62 publications
7
54
2
Order By: Relevance
“…Some forms of ASD are thought to result from an imbalance between excitation and inhibition (E-I) in synaptic transmission and cortical circuitry (Lee et al, 2017;Nelson and Valakh, 2015;Rubenstein and Merzenich, 2003), although a recent report suggests E-I imbalance is not causative in some mouse models (Antoine et al, 2019). E-I imbalance, and its modulation by various treatments, have been reported in BTBR mice (Burket et al, 2013;Lee et al, 2017;Silverman et al, 2012Silverman et al, , 2013.…”
Section: Av Reduces Neuronal Excitability In the Prefrontal Cortex Omentioning
confidence: 99%
“…Some forms of ASD are thought to result from an imbalance between excitation and inhibition (E-I) in synaptic transmission and cortical circuitry (Lee et al, 2017;Nelson and Valakh, 2015;Rubenstein and Merzenich, 2003), although a recent report suggests E-I imbalance is not causative in some mouse models (Antoine et al, 2019). E-I imbalance, and its modulation by various treatments, have been reported in BTBR mice (Burket et al, 2013;Lee et al, 2017;Silverman et al, 2012Silverman et al, , 2013.…”
Section: Av Reduces Neuronal Excitability In the Prefrontal Cortex Omentioning
confidence: 99%
“…There is, however, substantial experimental evidence that support the prediction that plasticity of excitatory synapses drives a "rebalancing" of inhibitory weights-consistent with the notion of an ontogenetically determined balance (Froemke et al, 2007;Froemke, 2015;Antoine et al, 2019;Chiu et al, 2019). For example, after induction of excitatory plasticity inhibitory synapses onto excitatory neurons "rebalance" over the course of minutes (Froemke et al, 2007).…”
Section: Conclusion and Experimental Predictionsmentioning
confidence: 74%
“…Previous work on mouse models of tuberous sclerosis (Bateup et al., 2011, 2013) or ASDs (Gkogkas et al., 2013) reported that dysregulated mTOR signaling can lead to an imbalance in the E‐I ratio. However, it is not clear whether this results primarily from an increase in excitatory function or a reduction of inhibition, as the E‐I ratio is subject to homeostatic compensation over time in transgenic models (Antoine et al., 2019). In contrast, the extremely precise spatiotemporal control of gene expression afforded by our in vivo single‐cell electroporation approach can reveal effects that, at least initially, are less impacted by compensation.…”
Section: Resultsmentioning
confidence: 99%